2016
DOI: 10.1021/acs.jcim.6b00524
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamic Nonprime Binding of Sampatrilat to the C-Domain of Angiotensin-Converting Enzyme

Abstract: Sampatrilat is a vasopeptidase inhibitor that inhibits both angiotensin I-converting enzyme (ACE) and neutral endopeptidase. ACE is a zinc dipeptidyl carboxypeptidase that contains two extracellular domains (nACE and cACE). In this study the molecular basis for the selectivity of sampatrilat for nACE and cACE was investigated. Enzyme inhibition assays were performed to evaluate the in vitro ACE domain selectivity of sampatrilat. The inhibition of the C-domain (K = 13.8 nM) by sampatrilat was 12.4-fold more pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 42 publications
0
30
0
Order By: Relevance
“…A previous study compared the affinity and selectivity of sampatrilat and samAsp for cACE and nACE 18. This reported that sampatrilat inhibited both cACE and nACE in the low nanomolar range, but it was 12.4‐fold more selective for cACE ( K i of 13.8 and 171.9 n m respectively).…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…A previous study compared the affinity and selectivity of sampatrilat and samAsp for cACE and nACE 18. This reported that sampatrilat inhibited both cACE and nACE in the low nanomolar range, but it was 12.4‐fold more selective for cACE ( K i of 13.8 and 171.9 n m respectively).…”
Section: Resultsmentioning
confidence: 98%
“…However, the molecular dynamics study predicted movement away from the docked poses, which is inconsistent with the crystal structures. This is probably because there are important water‐/ion‐mediated interactions in the crystal structures, which are not accounted for in the molecular modelling study 18.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations